Probiotics Augment the Effect of Non‐Surgical Periodontal Treatment—A Randomised, Double‐Blinded, Placebo‐Controlled Trial - Lundtorp‐Olsen, Christine Marie; Andersen; Sara Vallentin Raae; Massarenti, Laura; Gürsoy, Mervi; van Splunter, Annina; Bikker, Floris J.; Gursoy, Ulvi Kahraman; Markvart, Merete; Damgaard, Christian; Belstrøm, Daniel (Wiley, 2026)
Aim: To determine the effect of probiotic lozenges containing Lacticaseibacillus rhamnosus PB01, Latilactobacillus curvatus EB10 and xylitol after non-surgical periodontal treatment (NSPT) on changes in microbial composition. The secondary aims were to assess the clinical and immunological impact of probiotic consumption.
Materials and methods: Eighty adults with stage II or III periodontitis were enrolled and received NSPT at baseline, followed by a 12-week consumption of probiotics or placebo. Microbial sampling and clinical examination were performed at baseline, Week 6 and Week 12. The subgingival microbiota was analysed using 16S sequencing, the salivary microbiota by metagenomic sequencing and selected cytokines and proteases in saliva by bead-based immunoassay.
Results: Sixty-one participants completed the trial (probiotics n = 32, placebo n = 29). At Week 12, Treponema socranskii, Selenomonas sputigena, Dialister pneumosintes, Dialister invisus, Anaeroglobus geminatus and Fusobacterium nucleatum were significantly associated with the placebo group, while Streptococcus sanguinis, Neisseria elongata and Neisseria oralis were associated with the probiotic group. Bleeding on probing percentage (BoP%) and number of periodontal pockets (PPD) ≥ 5 mm decreased significantly more in the probiotic group compared to the placebo group (p < 0.05).
Conclusion: The tested probiotic supplement resulted in an additional short-term decrease in periodontitis-associated species along with greater improvements in BoP% and PPD ≥ 5 mm 12 weeks post-NSPT, compared to the placebo group.